Assessment of glycemic control in patients with type 2 Diabetes Mellitus: Glycemic control of patients with type 2 Diabetes - da Silva Santos, Maria Eduarda (2024)
Introduction: Strict control of blood glucose concentration prevents the onset and progression of microvascular complications related to type 2 diabetes mellitus (DM2). Objectives: The aim of this study was to evaluate the frequency of patients with DM2 treated in primary health care (PHC) of the Unified Health System (UHS) who have adequate glycemic control. Materials and methods: A cross-sectional study was carried out, lasting five months, in the PHC of the SUS in the municipalities of Bernardino de Campos and Salto Grande, SP. Inclusion criteria were: medical diagnosis of DM2, age > 18 years, having performed fasting blood glucose and glycated hemoglobin (HbA1c) tests less than 12 months before data collection, being treated at the study health units. Results: 1313 patients were aged > 18 years and had a medical diagnosis of DM2; however, 547 of these patients had undergone fasting blood glucose and HbA1c tests more than 12 months before data collection, and consequently, did not meet all inclusion criteria. Six hundred and three patients met all inclusion criteria and agreed to participate in the study. It was found that 190 patients (31.5%) had fasting blood glucose and HbA1c within the target recommended by the guidelines of the Brazilian Society of Diabetes (SBD). Conslusions: The results showed that a large number of patients with DM2 do not achieve adequate glycemic control, and do not perform fasting blood glucose and HbA1c tests at the frequency recommended by the SBD, requiring the adoption of new strategies to change this scenario.